Significantly improved black phase stability of FAPbI3 nanowires via spatially confined vapor phase growth in nanoporous templates. Issue 32 (7th August 2018) - Gu, Leilei; Zhang, Daquan; Kam, Matthew; Zhang, Qianpeng; Poddar, Swapnadeep; Fu, Yu; Mo, Xiaoliang; Fan, Zhiyong
Abstract : High-quality α-FAPbI3 nanowire arrays were fabricated and their stability was significantly improved by passivation and spatial confinement of nanotemplates. Abstract : The formamidinium lead iodide (FAPbI3 ) perovskite has attracted immense research interest as it has much improved stability than methylammonium lead iodide (MAPbI3 ) while still maintaining excellent optoelectronic properties. Compared to MAPbI3, FAPbI3 has shown an elevated decomposition temperature and a slower decomposition process and therefore it is considered as a more promising candidate for future high-efficiency and reliable optoelectronic devices. However, these excellent optoelectronic properties only exist in the alpha phase and this phase will spontaneously transform into an undesired delta phase with much poorer optoelectronic properties regardless of the environment. This is the main challenge for the application of the FAPbI3 perovskite. Herein, we report a novel strategy to stabilize the cubic black phase of FAPbI3 by using nanoengineering templates. Without further treatment, the black phase can be held over 7 months under ambient conditions and 8 days in an extreme environment with a Relative Humidity (RH) of 97%. A systematic study further reveals that this great improvement can be attributed to the spatial confinement in anodized alumina membrane (AAM) nanochannels, which prohibits the unwanted α-to-δ phase transition by restricting the expansion of NWs in the ab plane, and the excellent passivation against water molecule invasion. Meanwhile, we also demonstrate the potency of these NWs in practical applications by configuring them into photodetectors, which have shown reasonable response and excellent device stability.